Identifying sustainability traditional solutions of Dhamar house - Ahmed Abdurabu AL-Nehmi (International Journal of Rural and Regional Development, 2024)
The world is facing numerous issues from environment pollution, from natural disasters resulting, from climate change, and from the waste of natural resources, has focused specific attention to sustainable development. The house design has different characteristics according to the culture and environmental conditions. The study attempts to answer that, is the traditional architecture of Yemen consists with the principles of sustainable architecture? Moreover, what are sustainable solutions used in the traditional architecture of Dhamar houses? This study aims to evaluate the identity of traditional houses in Dhamar city and analyzes the positive features that can be developed in sustainable development, and extracting solutions of sustainability to improve the environment built in the modern. The methodology consists of literature studies and field observations. It is used a qualitative method that emphasizes identifying the characteristics of traditional architecture in Dhamar and its response to the environment and sustainability through literature and field studies that include observation and then questionnaires survey of 55 solutions as form questions. The study results show that traditional houses are very friendly to the environment and sustainability based on local resources, with positive design techniques using natural materials from the surrounding environment. The results indicate that both the houses owners and architects agree on Yemeni architecture as sustainability. The results show that the first principle is the economic principle, then social principle and environment principle. These research findings will increase insight into the concept of sustainable building design in the future.
Keywords: Architecture; Dhamar; Sustainability; Yemen; sustainable development; tower house; tradition